Mental health problems, sleep quality and overuse injuries in advanced Swedish rock-climbers - the CLIMB study - Identeg, F.; Nigicser, I.; Edlund, K.; Forsberg, N.; Sansone, M.; Tranaeus, U.; Hedelin, H. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Objectives To examine the prevalence of mental health problems (depression, anxiety, and stress), sleep quality, and disability due to overuse injuries in advanced and elite rock-climbers. The rock-climbers were compared to a group of non-climbing controls.